Recommending personalized informative contents on iTV - Campelo, D. (2018)
This paper aims to present an ongoing PhD research of the Doctoral Program Information and Communication in Digital Platforms and proposes a context aware recommender system (CARS) of informative contents about Assistance Services of General Interest for the Elderly (ASGIE) [6], for later exhibition on an Interactive TV (iTV) platform. The first phase of this research has been dedicated to assessing the information needs of seniors and designing a proper CARS data model. Future work will involve designing and implementing a prototype for further evaluation in the field with seniors, in the context of the +TV4E project [20]. In addition, it is intended to study the feasibility of leveraging the prototype over the Catchup TV service built in the UltraTV project [2]. The intended contribution of this doctoral research is to promote greater autonomy, wellbeing and info-inclusion of seniors through a personalized approach.